تفاعل الشباب الجزائري مع احداث طوفان الاقصىعبر مواقع التواصل الاجتماعي - صبرينة مسعودي; محجوبة زغدود; د/ ايت قاسي ذهبية (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة باللغة العربية هدفت دراستنا إلىمعرفة مظاهر تفاعل الشباب الجزائري لمواقع التواصل الاجتماعي في دعم القدس والقضية الفلسطينية خاصة بعد التطور الأخير المتمثل في طوفان الأقصى، وذلك من خلال معرفة: كيف يتفاعل الشباب الجزائري بمدينة الأغواط مع أحداث طوفان الأقصى عبر منصات مواقع التواصل الإجتماعي، ومعرفة المنصات الأكثر إعتماداوإستخداما لمتابعة أحداث طوفان الأقصى، واكتشاف العوائق التي تحول دون تمكن الشباب الجزائريين من التعبير عن دعمهم لطوفان الأقصى بصفة خاصة والقضية الفلسطينية بصفة عامة على أرض الواقع. تنتمي إلى مجموع الدراسات الوصفية المسحية، لذلك كان المنهج الملائم لها هو المنهج المنهج المسحي، وبالنظر لكون مجتمع الشباب في مدينة الأغواط كبير جداً يصعب حصره، اخترنا منه عينة قصدية. والأداة المستخدمة لجمع البيانات الميدانية في دراستنا هي استمارة الاستبيان وذلك لأنها تناسب غرض الدراسة وهدفها، إضافةً لما تتميز به من خصائص تسهل على الباحث والمبحوث اقتصاد الوقت والجهد، وتم توزيع إستمارةالإستبيان يدويا على عينة قدرت ب 62 فردا. من خلال الدراسة التي قمنا بها توصلنا إلى : 1) يتفاعل الشباب بمدينة الأغواط مع أحداث طوفان الأقصى عبر مواقع (منصات) التواصل التواصلالإجتماعي، عن طريق : • نشر مواضيع يحاولون من خلالها إظهار دعمهم وتضامنهم مع عملية طوفان الأقصى. • وأيضا يساهم شباب مدينة الأغواط في متابعة عملية طوفان الأقصى ( ماديا، ومعنويا، وإعلاميا). وهم على إطلاع دائم بالتطورات الحاصلة على الساحة الفلسطينية ( خاصة عملية طوفان الاقصى). 2) تماثلات الشباب بمدينة الأغواط مع أحداث طوفان الأقصى تمثلت في: • كانت ردة فعل شباب مدينة الأغواط عند تلقي خبر عملية طوفان الأقصى إيجابية ( الشعور بالسعادة) لدرجة كبيرة. • كتابة منشورات وتغيير صور البروفايل تضامنا مع أحداث طوفان الأقصى، وكذلك إنشاء مجموعات لدعم أحداث طوفان الأقصى. • فتح صفحات خاصة للتضامن مع أحداث طوفان الأقصىى. 3) المواقع (المنصات) الأكثر إعتماداوإستخداما لمتابعة أحداث طوفان الأقصى من طرف شباب مدينة الأغواط هي بالترتيب ( فيسبوك، تويتر، تيك توك)، ومن العراقيل التي تواجههم أثناء تفاعلهم مع أحداث طوفان الأقصى هي ( حذف المنشورات، حجب الحساب، تقييد الحساب). الكلمات المفتاحية: تفاعل، طوفان الأقصى، مواقع التواصل الإجتماعي. Summary of the study in English Our studyaimed to know the aspects of Algerian youth’s interaction with social networking sites in support of Jerusalem and the Palestinian cause, especiallyafter the recentdevelopmentrepresented by the Al-Aqsa Flood, by knowing: How Algerian youth in the city of Laghouat interactedwith the Al-Aqsa Flood eventsthrough social media platforms, and knowing the mostreliableplatforms. Usingit to follow up on the events of Al-Aqsa Flood, and discover the obstacles thatprevent Algerian youthfromexpressingtheir support for Al-Aqsa Flood in particular and the Palestinian cause in general on the ground. It belongs to a group of descriptive surveystudies, so the appropriatemethod for itwas the surveymethod. Giventhat the youthcommunity in the city of Laghouat isvery large and difficult to limit, we chose a purposivesamplefromit. The toolused to collectfield data in ourstudyis the questionnaire formbecauseitsuits the purpose and objective of the study, in addition to itscharacteristicsthatmakeiteasier for the researcher and the researched to save time and effort. The questionnaire formwasdistributedmanually to a sampleestimatedat 62 individuals. Through the studyweconducted, wefound: 1) Youth in the city of Laghouat interactwith the events of the Al-Aqsa Flood via social media platforms, via: • Publishingtopics in whichtheytry to show their support and solidaritywith the Al-Aqsa Flood operation. • The youth of the city of Laghouat alsocontribute to following up on the Al-Aqsa flood operation (financially, morally, and medially). They are constantlyinformed of developmentstaking place in the Palestinianarena (especially the Al-Aqsa flood operation). 2) The similarities of young people in the city of Laghouat with the events of the Al-Aqsa flood wererepresented in: • The reaction of the youth of the city of Laghouat uponreceiving the news of the Al-Aqsa Flood operationwas positive (feeling happy) to a greatextent. • Writingposts and changing profile pictures in solidaritywith the Al-Aqsa Flood events, as well as creating groups to support the Al-Aqsa Flood events. • Openingspecial pages in solidaritywith the events of the Al-Aqsa Flood. 3) The platformsmostreliedupon and used to follow the events of the Al-Aqsa Flood by the youth of the city of Laghouat are, in order, (Facebook, Twitter, TikTok), and among the obstacles they face duringtheir interaction with the Al-Aqsa Flood events are (deletingposts, blocking the account, restricting the account). Keywords: interaction, Al-Aqsa flood, social networking sites.
دراسة ميدانيةلعينة من الشباب بمدينة الاغواط